Acceptance and commitment therapy (ACT) for patients with chronic renal failure - Fourni Ardiansyah; Shinta Shinta; Dita Amita (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Patients with chronic renal failure who undergo physiological haemodialysis will experience unstable blood pressure, nausea, low haemoglobin value, cramped legs, difficulty sleeping, and dizziness when waking up. The patient feels tired, anxious, and then discovered the symptoms of fatigue and depression lead to a feeling of powerlessness.Purpose: To know of acceptance and commitment therapy (ACT) for patients with chronic renal failure and a response to perceived powerlessness.Method: A quantitative study by a one-group pre-experimental design with a sample of 25 participants as patients with chronic renal failure under haemodialysis at Harapan dan Do'a Hospital. The sampling technique used was purposive sampling. The assessment of the response to powerlessness used a Likert scale questionnaire. The acceptance and commitment therapy (ACT) delivered for 4 sessions.Results: The proof that there is a decrease in the score of powerlessness responses after acceptance and commitment therapy with a p-value of 0.00 and a different means after the intervention of 1.72Conclusion: There is an influence of commitment therapy (ACT) for patients with chronic renal failure and a response to perceived powerlessness.Hospital management to consider applying an acceptance and commitment therapy, and nurses to have a course that therapy especially nurses who conducted with chronic patients.